The Performance of Broiler Chickens with The Addition of Dayak Onion Extract in Drinking Water - Zakiyatulyaqin Zakiyatulyaqin; Marjoko Purnomosidi; Duta Setiawan (UNIVERSITAS ISLAM LAMONGAN, 2020)
This research was conducted to study the ability of Dayak onion extract added to drinking water on the performance of body weight gain, feed consumption, and water consumption of broiler chickens. The experiment used 80 DOC broiler aged 4 days from strain Abror Acres CP 707, using complete randomized design (RAL) with 5 treatments and 4 replicated of 0 gr, 5 gr, 10 gr, 15 gr and 20 gr Dayak onion extract per day. Feed and drinking water were given on ad libitum. Data were analyzed by using the Analysis of Variance (ANOVA) and significant effect was tested with Duncan's New Multiple Rang Test. The results of this study showed that giving Dayak onion extract with level of 0 gr, 5 gr, 10 gr, 15 gr and 20 gr in broiler chickens provided no significant difference (p>0,5) on body weight gain, feed consumption, and water consumption. The conclusion of this research is giving the level of Dayak onion extract on the drinking water does not significantly (P>0,05) affect the body weight gain, feed consumption, and water consumption of broiler chicken.